Fusion of fluorescent protein to puromycin N-acetyltransferase is useful in Drosophila Schneider S2 cells expressing heterologous proteins - Nagahashi, Kotomi (Springer Netherlands, 2012)
The Drosophila melanogaster Schneider 2 (S2) cell line was established in 1972. Many studies have indicated that generation of recombinant proteins with S2 cells is more desirable than using other methods, since native proteins derived from S2 cells do not usually interact with those derived from mammalian cells. In order to minimize the duration for selections, we established an all-in-one single plasmid pMT-PURO, which enables to express the gene of interest as well as a selection gene “pac”. However, there is a weak point in the system. In order to verify the hallmark of the transformed cells, puromycin selection as well as verification of the gene of interests is still necessary. To improve this situation, we generated pMT-PURO2G and pMT-PURO2R, which enable to verify the hallmark of the transformed cells during the selections by the detection of enhanced green fluorescent protein (EGFP) or DsRED2. This new system gives reliable and reproductive results for recombinant protein synthesis and gets rid of some degree of uncertainty for the outcome of the transfection.